A Curcumin‐Modified Coordination Polymers with ROS Scavenging and Macrophage Phenotype Regulating Properties for Efficient Ulcerative Colitis Treatment - Hang Yao; Feifei Wang; Hui Chong; Jingjing Wang; Yang Bai; Meng Du; Xiaohui Yuan; Xiaofei Yang; Ming Wu; Yuping Li; Huan Pang (Advanced Science, 2023)
Abstract Overexpression of classically activated macrophages (M1) subtypes and assessed reactive oxygen species (ROS) levels are often observed in patients with ulcerative colitis. At present, the treatment system of these two problems has yet to be established. Here, the chemotherapy drug curcumin (CCM) is decorated with Prussian blue analogs in a straightforward and cost‐saving manner. Modified CCM can be released in inflammatory tissue (acidic environment), eventually causing M1 macrophages to transform into M2 macrophages and inhibiting pro‐inflammatory factors. Co(III) and Fe(II) have abundant valence variations, and the lower REDOX potential in CCM‐CoFe PBA enables ROS clearance through multi‐nanomase activity. In addition, CCM‐CoFe PBA effectively alleviated the symptoms of UC mice induced by DSS and inhibited the progression of the disease. Therefore, the present material may be used as a new therapeutic agent for UC.